PENGARUH KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) UNIT KEGIATAN OLAHRAGA MAHASISWA (UKOM) SEPAK BOLA UNIVERSITAS KRISTEN INDONESIA - Muhammad Gilang Andrean; Desideria Regina; Nenny Anggraini (Universitas Kristen Indonesia, 2023)
Human resources are the main cause in running an association, where human resources become thinkers, movers, and planners to determine the development of the organization in a better direction. Members are less motivated in training, Members' organizational commitment is low, the authors hope UKOM UKI students can improve quality both individually and as a team according to predetermined targets. This testing mode uses a causal association mode, then it is carried out quantitatively. The causal association mode is a test that is used to measure facts to what extent is related between one variable or several variables. A causal relationship is a relationship that affects the cause. Organizational commitment and motivation have a good influence on the OCB members of the UKOM UKI football organization. Based on the results of the study, it was found that there are effects and causes between commitment, motivation, to OCB, especially at UKOM UKI football. It is known that simultaneously commitment has a significant effect on OCB, tcount ˃ ttable is 6.218˃ 2.048 with a significance level of 0.05% <5% . It can be seen that overall motivation has a significant effect on organizational citizenship behavior with a t count ˃ t table which is 8.842 ˃ 2.048 with a significant level of 0% <5%. Keywords: organizational commitment, motivation, organizational citizenship behaviour.